2006
DOI: 10.1016/j.ydbio.2006.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Neural induction in Xenopus requires inhibition of Wnt-β-catenin signaling

Abstract: Canonical Wnt signals have been implicated in multiple events during early embryogenesis, including primary axis formation, neural crest induction, and A-P patterning of the neural plate. The mechanisms by which Wnt signals can direct distinct fates in cell types that are closely linked both temporally and spatially remains poorly understood. However, recent work has suggested that the downstream transcriptional mediators of this pathway, Lef/Tcf family DNA binding proteins, may confer distinct outcomes on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 84 publications
3
47
1
Order By: Relevance
“…First, Smad5-sbn induces neural tissue in the absence of dorsal mesoderm markers, making indirect neural induction in our paradigm highly unlikely. Second, the lack of repression of chordin and goosecoid expression by Smad5-sbn indicates that it does not inhibit Wnt and Nodal signaling, which are known to regulate these genes and limit neural specification (11,19,20). Therefore, in absence of current contradictory evidence, we suggest that Smad5-sbn acts as a specific and powerful BMP inhibitor.…”
Section: Discussionmentioning
confidence: 79%
“…First, Smad5-sbn induces neural tissue in the absence of dorsal mesoderm markers, making indirect neural induction in our paradigm highly unlikely. Second, the lack of repression of chordin and goosecoid expression by Smad5-sbn indicates that it does not inhibit Wnt and Nodal signaling, which are known to regulate these genes and limit neural specification (11,19,20). Therefore, in absence of current contradictory evidence, we suggest that Smad5-sbn acts as a specific and powerful BMP inhibitor.…”
Section: Discussionmentioning
confidence: 79%
“…That said, inhibition of canonical Wnt signaling appears to be required for neural induction. 120 In the embryo, both the requirement for Wnt signaling (for neural crest induction) and its inhibition (in neuroectoderm) are likely to be influenced by the presence of the B1-type Sox proteins, Sox2 and Sox3 (Fig. 5).…”
Section: Neural Crest Induction and Migration In Xenopusmentioning
confidence: 99%
“…In support of Wnt signaling having a role in maintaining the pluripotency of mouse ES cells, the genetic ablation of both Gsk3a and Gsk3b or the pharmacological inhibition of GSK3 in these cells promotes their self-renewal and blocks neural differentiation (Aubert et al, 2002;Doble et al, 2007;Haegele et al, 2003;Sato et al, 2004;Ying et al, 2008). Consistent with this notion, experiments in Xenopus and mouse embryos have revealed that Wnt signaling prevents neural development (Haegele et al, 2003;Heeg-Truesdell and LaBonne, 2006;Itoh and Sokol, 1999;Yoshikawa et al, 1997).…”
Section: Introductionmentioning
confidence: 95%